Component addition polymerization

By gradually adding monomer feed solution during suspension polymerization, the distribution of polymer units is controlled, and the problems of unevenness and insufficient mechanical strength of polymer beads are solved, high crushing strength and permeability are achieved, and the beads are improved Overall performance.

CN111712526BActive Publication Date: 2025-01-07DDP SPECIALTY ELECTRONICS MATERIALS US LLC +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201880083104.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-11-10
Filing Date
2018-10-24
Publication Date
2025-01-07
Estimated Expiration
2038-10-24

AI Technical Summary

Technical Problem

Existing suspension polymerization methods lead to inhomogeneity of polymer beads and insufficient mechanical strength, especially after functionalization, which is sensitive to permeability stress and prone to rupture.

Method used

The polymer bead aggregate method of 75 to 99% monofunctional vinyl monomer and 1 to 25% polyfunctional vinyl monomer is used to gradually add the monomer feed solution during the polymerization process in the monomer droplets. , control the distribution uniformity and reaction degree of polymerization units to ensure the high crushing strength and permeability of the beads.

Benefits of technology

The relatively uniform distribution and high mechanical strength of polymer beads are achieved, which reduces the fracture caused by permeability stress and improves the overall performance of beads.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002550105100000052
    Figure BDA0002550105100000052
  • Figure BDA0002550105100000071
    Figure BDA0002550105100000071
  • Figure BDA0002550105100000072
    Figure BDA0002550105100000072
Patent Text Reader

Abstract

A collection of polymer beads is provided, wherein the beads comprise (i) 75 to 99 weight percent, based on the weight of the beads, of polymerized units of monofunctional vinyl monomers, and (ii) 1 to 25 weight percent, based on the weight of the beads, of polymerized units of polyfunctional vinyl monomers; wherein within each bead, the average molar concentration of polymerized units of polyfunctional vinyl monomers per cubic micrometer is MVAV; wherein, within each bead, T1000 is a sequence of 1,000 uniquely linked polymerized monomer units; wherein, within each T1000, MVSEQ is the weight percentage of polymerized units of polyfunctional vinyl monomers, based on the weight of T1000; wherein MVRATIO = MVSEQ / MVAV; and wherein 90 volume percent or more of the beads are uniform beads, wherein uniform beads are beads in which 90% or more of all T1000 sequences have an MVRATIO of 1.5 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] A useful method for producing polymer beads is suspension polymerization, which is a method in which a monomer droplet is suspended in an aqueous medium, and then the monomers in the droplet are polymerized to form polymer beads. When a monomer mixture is present in a monomer droplet, it is known that monomers generally react at different rates to form non-uniform polymer beads. For example, it is expected that one or more regions in the droplet can form a copolymer having a higher ratio of polymerized units of a higher reactive monomer than the average ratio of the higher reactive monomer present in the monomer mixture in the entire droplet. It is expected that such regions rich in polymerized units of a higher reactive monomer will be particularly likely to form in the early stages of the polymerization process. It is further expected that in the later stages of the polymerization process, relatively weak regions of polymerized units of a higher reactive monomer will be formed. Therefore, it is expected that the resulting polymer beads will be non-uniform, wherein some polymer segments in the beads have polymerized units of a higher reactive monomer at different concentrations than other polymer segments. It is expected that this non-uniformity will be harmful to some performance characteristics of the polymer beads.

[0002] It is desirable to provide a method of preparing polymer beads, the method comprising polymerization of a monomer mixture to obtain polymer beads in which the distribution of polymerized units of each monomer is relatively uniform. More generally, it is further desirable to provide a method by which the degree and nature of heterogeneity can be controlled, rather than relying solely on the relative reactivity of the monomers to produce uncontrolled heterogeneity. It is also desirable to provide a method in which mass transfer of monomers fed to monomer droplets where polymerization occurs during polymerization is carried out efficiently or consistently or efficiently and consistently, where "consistently" means that the mass transfer is carried out unusually nearly identically from one batch (i.e., one polymerization process) to another batch to another.

[0003] In many cases, after polymerization is complete, the polymer beads are functionalized. That is, the polymer beads are subjected to one or more chemical reactions to attach ionic functional groups to the polymer beads, which may be anionic or cationic groups.

[0004] An important characteristic of polymer beads is mechanical strength. The mechanical strength of polymer beads can be evaluated immediately after polymerization, or the mechanical strength of functionalized beads can be evaluated. The mechanical strength of beads can be measured directly, for example by measuring the force required to crush the beads. Higher crushing strength is desirable, especially for functionalized beads. Moreover, the mechanical strength of the beads can be measured by exposing polymer beads functionalized with anionic or cationic groups to alternating solutions containing different types of ions. Exposure to these alternating solutions can cause osmotic stress, resulting in the rupture of some polymer beads. It is desirable that as few functionalized beads as possible rupture due to osmotic stress.

[0005] US 3,792,029 describes a suspension polymerization process wherein during suspension polymerization of a monomer mixture, an emulsion containing a more reactive monomer is added to the suspension as polymerization occurs. It would be desirable to provide a process wherein pure monomer is added to the suspension polymerization process. It would also be desirable to provide polymer beads having one or more of the following advantages: relatively uniform distribution of polymerized units of each monomer, high crush strength, consistent and / or efficient mass transfer of monomer feed to the monomer droplets, and / or high resistance to osmotic stress.

[0006] In addition, in the method described in US 3,792,029, the emulsion added to the suspension during polymerization contains a mixture of monomers with higher reactivity and monomers with lower reactivity. In the mixture added to the suspension described in US 3,792,029, there is significantly more (by weight) monomers with lower reactivity than monomers with higher reactivity. It is believed that the method described in US 3,792,029 may lead to one or more of the following undesirable effects: the method may lead to an increase in bead size, which imposes undesirable stress on the polymer network; and / or the method may lead to the formation of inhomogeneities in the bead structure, for example by forming an interpenetrating polymer network. It is desirable to provide a method in which the monomer added to the suspension during polymerization is 50% by weight or more of a monomer with higher reactivity. It is also desirable to provide a method that avoids the undesirable effects of the method of US 3,792,029.

[0007] The following is a statement of the invention.

[0008] A first aspect of the present invention is a method for preparing an assembly of polymer beads, wherein the beads comprise

[0009] (i) 75 to 99 wt. % of polymerized units of monofunctional vinyl monomers, based on the weight of the beads, and

[0010] (ii) from 1 to 25 wt. % of polymerized units of a polyfunctional vinyl monomer, based on the weight of the beads,

[0011] wherein the method comprises

[0012] (a) providing an aqueous suspension of monomer droplets comprising an initiator, a monofunctional vinyl monomer, and a polyfunctional vinyl monomer;

[0013] (b) initiating polymerization of the monomers in the monomer droplets;

[0014] (c) adding a monomer feed solution to the suspension while polymerization of the monomer in the monomer droplets occurs

[0015] wherein the addition is started when the degree of polymerization of the monomer in the monomer droplets (EXTSTART) is between 0% and 50%, and

[0016] wherein the adding is terminated when the degree of polymerization of the monomer in the monomer droplets (EXTSTOP) is between 5% and 100% after EXTSTART;

[0017] wherein the feed solution comprises the monomer in an amount of 90 wt % to 100 wt % based on the weight of the feed solution;

[0018] The feed solution includes the multifunctional vinyl monomer in an amount of 50 wt % to 100 wt % based on the weight of the feed solution.

[0019] A second aspect of the present invention is a method for preparing an assembly of polymer beads, wherein the beads comprise

[0020] (i) 75 to 99 wt. % of polymerized units of monofunctional vinyl monomers, based on the weight of the beads, and

[0021] (ii) from 1 to 25 wt. % of polymerized units of a polyfunctional vinyl monomer, based on the weight of the beads,

[0022] wherein the average molar concentration of polymerized units of the multifunctional vinyl monomer per cubic micrometer in each bead is MVAV;

[0023] where, within each bead, T1000 is a sequence of 1,000 uniquely linked polymerized monomer units;

[0024] wherein, within each T1000, MVSEQ is the weight percent of polymerized units of the multifunctional vinyl monomer, based on the weight of T1000;

[0025] Where MVRATIO = MVSEQ / MVAV;

[0026] and

[0027] Wherein 90% by volume or more of the beads are homogeneous beads, wherein homogeneous beads are beads wherein 90% or more of all T1000 sequences have an MVRATIO of 1.5 or less.

[0028] A third aspect of the invention is a method of treating water, wherein the water comprises dissolved ions, the ions comprising undesirable cations, wherein the method comprises

[0029] (a) providing a functionalized polymer bead assembly comprising

[0030] (i) 75 to 99 wt. % of polymerized units of monofunctional vinyl monomers, based on the weight of the beads, and

[0031] (ii) from 1 to 25 wt. % of polymerized units of a polyfunctional vinyl monomer, based on the weight of the beads,

[0032] (iii) a functional group bound to the polymer beads and having a charge opposite to that of the undesired ion, and

[0033] (iv) ions that are not bound to the polymer beads and have the same charge as the undesired ions;

[0034] wherein the average molar concentration of polymerized units of the multifunctional vinyl monomer per cubic micrometer in each bead is MVAV;

[0035] where, within each bead, T1000 is a sequence of 1,000 uniquely linked polymerized monomer units;

[0036] wherein, within each T1000, MVSEQ is the weight percent of polymerized units of the multifunctional vinyl monomer, based on the weight of T1000;

[0037] Where MVRATIO = MVSEQ / MVAV;

[0038] and

[0039] wherein 90% by volume or more of the beads are homogeneous beads, wherein a homogeneous bead is a bead wherein 90% or more of all T1000 sequences have an MVRATIO of 1.5 or less;

[0040] (b) then passing the water through a bed of polymer beads to exchange the undesirable ions for ions (iv),

[0041] (c) A regeneration solution comprising dissolved ions (v) of the same species as ions (iv) is then passed through the bed of polymer beads to exchange ions (v) for undesirable ions.

[0042] A fourth aspect of the present invention is a method for producing 2,2-bis(4-hydroxyphenyl)propane, which comprises condensing phenol with acetone in the presence of an acid catalyst to produce the dihydric phenol 2,2-bis(4-hydroxyphenyl)propane;

[0043] wherein the acid catalyst comprises an aggregate of sulfonated polymer beads, wherein the sulfonated polymer beads comprise

[0044] (i) 75 to 99 wt. % of polymerized units of monofunctional vinyl monomers, based on the weight of the beads, and

[0045] (ii) from 1 to 25 wt. % of polymerized units of a polyfunctional vinyl monomer, based on the weight of the beads,

[0046] wherein the average molar concentration of polymerized units of the multifunctional vinyl monomer per cubic micrometer in each bead is MVAV;

[0047] where, within each bead, T1000 is a sequence of 1,000 uniquely linked polymerized monomer units;

[0048] wherein, within each T1000, MVSEQ is the weight percent of polymerized units of the multifunctional vinyl monomer, based on the weight of T1000;

[0049] Where MVRATIO = MVSEQ / MVAV;

[0050] and

[0051] Wherein 90% by volume or more of the beads are homogeneous beads, wherein homogeneous beads are beads wherein 90% or more of all T1000 sequences have an MVRATIO of 1.5 or less.

[0052] The following is a detailed description of the present invention.

[0053] As used herein, the following terms have the designated definitions unless the context clearly dictates otherwise.

[0054] As used herein, "polymer" is a relatively large molecule composed of the reaction product of smaller chemical repeating units. Polymers can have a structure that is linear, branched, star-shaped, cyclic, hyperbranched, cross-linked, or a combination thereof; polymers can have a single type of repeating unit (a "homopolymer") or they can have more than one type of repeating unit (a "copolymer"). Copolymers can have various types of repeating units arranged randomly, sequentially, in blocks, in other arrangements, or any mixture or combination thereof.

[0055] Molecules that can react with each other to form repeating units of a polymer are referred to herein as "monomers." The repeating units so formed are referred to herein as "polymerized units" of the monomer.

[0056] Vinyl monomers have the structure Where R 1 , R 2 , R 3 , and R 4 Each is independently hydrogen, a halogen, an aliphatic group (e.g., an alkyl group), a substituted aliphatic group, an aryl group, a substituted aryl group, another substituted or unsubstituted organic group, or any combination thereof. Vinyl monomers are capable of free radical polymerization to form polymers. Some vinyl monomers have R 1 , R 2 , R 3 and R 4Such vinyl monomers are referred to herein as multifunctional vinyl monomers. Vinyl monomers having exactly one polymerizable carbon-carbon double bond are referred to herein as monofunctional vinyl monomers.

[0057] Styrene monomers are vinyl monomers such as: 1 and R 2 Each is hydrogen, R 3 is hydrogen or alkyl and -R 4 With the following structure

[0058]

[0059] Where R 5 , R 6 , R 7 , R 8 , and R 9 Each is independently hydrogen, a halogen, an aliphatic group (eg, an alkyl group or a vinyl group), a substituted aliphatic group, an aryl group, a substituted aryl group, another substituted or unsubstituted organic group, or any combination thereof.

[0060] The reaction between monomers to form one or more polymers is referred to herein as a polymerization process.

[0061] As used herein, an initiator is a molecule that is stable under ambient conditions but is capable of generating one or more free radical-bearing fragments under certain conditions, and the fragments are capable of interacting with monomers to start a free radical polymerization process. Conditions that lead to the generation of free radical-bearing fragments include, for example, elevated temperature, participation in an oxidation-reduction reaction, exposure to ultraviolet and / or ionizing radiation, or a combination thereof.

[0062] As used herein, the phrase "total monomers" refers to all monomers used to prepare the polymer, including monomers present when polymerization initiation begins and all monomers that may be added during polymerization.

[0063] A polymer is considered herein to contain polymerized units of the monomers used to prepare the polymer, even if, after polymerization, some or all of these polymerized units are modified by the addition of one or more functional groups. For example, a copolymer prepared from styrene and DVB in a weight ratio of styrene:DVB of 90:10 is considered to have 90% by weight polymerized units of styrene. If the copolymer is subsequently modified by reaction with sulfuric acid to replace some of the hydrogen atoms on the aromatic rings with sulfonic acid groups, the resulting functionalized polymer is still considered to have 90% by weight polymerized units of styrene.

[0064] As used herein, an inhibitor is a molecule that reacts with vinyl monomer free radicals or with free radicals on a growing vinyl polymer chain to form new free radicals that do not participate in vinyl polymerization.

[0065] The macroporous polymer beads have a porous structure with an average pore size of 20 nm or more. The pore size is measured using the Brunauer-Emmett-Teller (BET) method with nitrogen. Macroporous polymer beads are typically prepared by incorporating a porogen into a monomer droplet. The porogen is soluble in the monomer, but the polymer is not soluble in the porogen, so as the polymer is formed, phase-separated domains of the porogen are retained. After polymerization, the porogen is removed by evaporation or by washing with a solvent. The porous structure of the polymer beads is the empty space left behind when the porogen is removed from its phase-separated domains.

[0066] The preparation of gel-type polymer beads does not use porogens. The pores in the gel-type polymer beads are the free volume between atoms in the entangled, possibly cross-linked polymer chains of the polymer beads. The pores in the gel-type polymer beads are less than 20 nm. In some cases, the pores in the gel-type resin are too small to be detected using the BET method.

[0067] Two ions or ionic groups are considered herein to have the "same" charge if both are anionic or if both are cationic, regardless of the magnitude of the charge. For example, a sulfonate ion (i.e., -SO3 - ) is considered to have the same 2- ) the same charge. Similarly, if one ion or ionic group is an anion and the other ion or ionic group is a cation, the two ions or ionic groups are considered to have "opposite" charges herein, regardless of the magnitude of the charges. A carboxylic acid group is considered to include a carboxylate anion and a hydrogen cation, and a sulfonic acid group is considered to include a sulfonate anion and a hydrogen cation).

[0068] As used herein, ion exchange is a process in which a solution is contacted with an ion exchange resin. Prior to contact with the solution, the ion exchange resin has functional groups of a certain charge and has ions of the opposite charge associated with the functional groups. When the solution is contacted with the ion exchange resin, some of the ions in the solution attach to the ion exchange resin through ion exchange sites of the same charge associated with the functional groups on the ion exchange resin.

[0069] A compound is referred to herein as water-soluble if 5 grams or more of the compound forms a stable solution in 100 ml of water at 25° C. In the case of some water-soluble polymers, it may be necessary to heat the water above 25° C. to dissolve the polymer, but after cooling to 25° C., the solution is stable when kept at 25° C.

[0070] A suspension is a composition having particles of a substance distributed in a liquid medium. The distributed particles may be liquid or solid; distributed liquid particles are referred to as droplets. A medium is "aqueous" if it contains 90% or more water by weight based on the weight of the medium. A suspension may or may not be stable. That is, the distributed particles may or may not have a tendency to settle to the bottom of a container or float to the top of a container, and mechanical agitation may or may not be required to keep the particles distributed in the medium.

[0071] Polymer beads are particles that contain 90% by weight or more of an organic polymer based on the weight of the particle. The polymer beads are spherical or nearly spherical. The polymer beads are characterized by their radius. If the bead is not spherical, the radius of the bead is taken herein to be the radius of a "reference sphere", which is an imaginary sphere of the same volume as the bead. Whether a particle is spherical is assessed by "sphericity", represented by the Greek letter Ψ. For a particle having a volume VP and principal axes of length a (long), b (medium) and c (short), the sphericity is

[0072]

[0073] As used herein, the unit of volume is "cubic micrometer" (abbreviated as μm 3 ) refers to the volume of a cube with a side length of 1 micrometer.

[0074] As used herein, "ambient temperature" is synonymous with "room temperature" and is about 23°C.

[0075] The aggregate of particles has a harmonic mean diameter (HMD) defined as:

[0076]

[0077] where n is the number of particles, and di is the diameter of the ith particle.

[0078] Ratios are characterized herein as follows. For example, if a ratio is considered to be 5:1 or higher, it means that the ratio can be 5:1 or 6:1 or 100:1, but not 4:1. To state this characterization in a general way, if a ratio is considered to be X:1 or higher, then the ratio is Y:1, where Y is greater than or equal to X. Similarly, for example, if a ratio is considered to be 2:1 or lower, it means that the ratio can be 2:1, or 1:1, or 0.001:1, but not 3:1. To state this characterization in a general way, if a ratio is considered to be Z:1 or lower, then the ratio is W:1, where W is less than or equal to Z.

[0079] The process of the present invention involves monomer droplets comprising a vinyl monomer and an initiator. The following is a description of the monomer droplets as they exist prior to initiating polymerization.

[0080] Preferably, the amount of monomer in the monomer droplet is 80 wt% or more based on the weight of the droplet; more preferably 90 wt% or more; more preferably 95 wt% or more.

[0081] Preferred vinyl monomers are styrene monomers, acrylic monomers and mixtures thereof. Preferably, all monomers used are selected from styrene monomers, acrylic monomers and mixtures thereof. More preferably, all monomers used are selected from styrene monomers. Vinyl monomers include one or more monofunctional vinyl monomers. Preferred monofunctional vinyl monomers are acrylic acid and styrene monofunctional monomers; more preferably monofunctional styrene monomers; more preferably styrene. Vinyl monomers also include one or more multifunctional vinyl monomers. Preferred multifunctional vinyl monomers are multifunctional styrene monomers; more preferably divinylbenzene. Preferably, the amount of vinyl chloride is 0 wt % to 0.1 wt %, more preferably 0 wt % to 0.01 wt % based on the total weight of all monomers; more preferably 0 wt %.

[0082] Preferably, the amount of styrene monomer in the droplets before initiation of polymerization is 50 wt % or more, based on the weight of all monomers in the droplets; more preferably 75 wt % or more; more preferably 88 wt % or more; more preferably 94 wt % or more; more preferably 97 wt % or more; more preferably 100 wt %.

[0083] Preferably, the amount of monofunctional vinyl monomers in the droplets before initiating polymerization is 75 wt% or more based on the weight of all monomers in the droplets; more preferably 80 wt% or more; more preferably 85 wt% or more; more preferably 90 wt% or more; more preferably 94 wt% or more. Preferably, the amount of monofunctional vinyl monomers in the droplets is 99.9 wt% or less based on the weight of all monomers in the droplets; more preferably 99 wt% or less; more preferably 98.5 wt% or less.

[0084] Preferably, the amount of the multifunctional vinyl monomer in the droplets before initiating polymerization is 0.1 wt% or more based on the weight of all monomers in the droplets; more preferably 1 wt% or more; more preferably 1.5 wt% or more. Preferably, the amount of the multifunctional vinyl monomer in the droplets is less than 25 wt% based on the weight of all monomers in the droplets; more preferably 20 wt% or less; more preferably 15 wt% or less; more preferably 10 wt% or less; more preferably 6 wt% or less.

[0085] It is useful to characterize the amount of multifunctional vinyl monomer ("MFMPRIROR") in the droplets prior to initiation of polymerization as a weight percent of total monomers. Preferably, MFMPRIOR is 0.1% or more; more preferably 0.5% or more; more preferably 1% or more; more preferably 1.5% or more; more preferably 2% or more. Preferably, MFMPRIOR is 10% or less; more preferably 8% or less; more preferably 6% or less.

[0086] It is also useful to characterize the ratio

[0087] MFMRATIO=100*MFMPRIOR / MFMTOTAL

[0088] Where MFMTOTAL is the total weight percent of multifunctional monomers used in the entire polymerization process, including multifunctional monomers present before initiation and multifunctional monomers added after initiation. Preferably, MFMRATIO is 10% or more; more preferably 20% or more; more preferably 30% or more. Preferably, MFMRATIO is 80% or less; more preferably 70% or less; more preferably 60% or less.

[0089] The method of the present invention involves a suspension of monomer droplets in an aqueous medium. Preferably, the total amount of monomer is 5 wt% or more based on the total weight of the suspension; more preferably 10 wt% or more; more preferably 15 wt% or more. Preferably, the total amount of monomer is 55 wt% or less based on the total weight of the suspension; more preferably 35 wt% or less; more preferably 30 wt% or less.

[0090] The monomer droplets contain one or more initiators. Preferred initiators have a solubility of 1 gram or less in 100 mL of water at 25°C; more preferably 0.5 gram or less; more preferably 0.2 gram or less; more preferably 0.1 gram or less. Preferred are organic peroxide and hydroperoxide initiators; more preferably peroxide initiators; more preferably benzoyl peroxide and its derivatives; more preferably benzoyl peroxide. Preferably, the weight ratio of initiator to total monomer is 0.0002:1 or higher; more preferably 0.0005:1 or higher; more preferably 0.001:1 or higher; more preferably 0.002:1 or higher. Preferably, the weight ratio of initiator to total monomer is 0.02:1 or lower; more preferably 0.01:1 or lower; more preferably 0.007:1 or lower.

[0091] The monomer droplets optionally contain one or more porogens. Preferably, little or no porogen is present. That is, preferably no porogen is present, or if present, the amount of porogen is 1 wt% or less based on the weight of the monomer droplet; more preferably 0.1 wt% or less. More preferably, no porogen is present in the monomer droplet.

[0092] Monomers normally supplied by manufacturers contain relatively small amounts of inhibitors to prevent accidental polymerization during storage. Common inhibitors are quinones (e.g. 1,4-benzoquinone) and hindered phenols (e.g. 4-tert-butylcatechol, also known as 4-tert-butylcatechol).

[0093] Preferably, before initiating polymerization, the monomer droplets either contain no polymer of any kind or contain a small amount of polymer of any kind. That is, if any polymer is present in the monomer droplets, preferably the total amount of polymer is 0.1 wt% or less based on the weight of the monomer droplets.

[0094] The aqueous medium preferably comprises one or more water-soluble polymers. Water-soluble polymers are believed to stabilize the monomer droplets to prevent coalescence. Suitable water-soluble polymers may be any of a variety of polymer types. Preferred water-soluble polymers are water-soluble polyvinyl alcohol polymers, water-soluble derivatives of cellulose, quaternary ammonium polymers, gelatin, and mixtures thereof. More preferred water-soluble polymers are water-soluble polyvinyl alcohol polymers, water-soluble derivatives of cellulose, and mixtures thereof. Among quaternary ammonium polymers, preferred are polymers of diallyldimethylammonium chloride (DADMAC). Among water-soluble derivatives of cellulose, preferred are carboxymethyl methylcellulose. Among polyvinyl alcohol polymers, preferred degrees of hydrolysis are those of 80% to 90%. Preferably, the aqueous medium comprises one or more water-soluble polyvinyl alcohol polymers and one or more water-soluble derivatives of cellulose.

[0095] When one or more water-soluble polymers are used, preferably, the total amount of water-soluble polymers is 0.02 wt% or more based on the weight of the aqueous medium; more preferably 0.05 wt% or more; more preferably 0.1 wt% or more. When one or more water-soluble polymers are used, preferably, the total amount of water-soluble polymers is 2 wt% or less based on the weight of water; more preferably 1 wt% or less; more preferably 0.5 wt% or less.

[0096] Other methods of stabilizing the monomer droplets are also suitable and can be used instead of or in addition to one or more water-soluble polymers. For example, solid particles smaller than the monomer droplets can reside on the surface of the droplets and stabilize the droplets. An example of such solid particles are colloidal silica particles.

[0097] The aqueous suspension of monomer droplets optionally contains one or more suspension aids. Suspension aids are believed to stabilize the monomer droplets. Suspension aids can be introduced by adding them to the aqueous phase or by adding them to the monomer droplets or by a combination thereof. Regardless of how the suspension aid is introduced, the preferred amount of suspension aid is 0.001 wt % to 0.1 wt % based on the weight of the monomer droplets. The preferred suspension aid is 4-vinylphenylboronic acid.

[0098] The nature of the step of initiating polymerization depends in part on the nature of the initiator used. For example, when a thermal initiator is used, the initiation conditions involve establishing a temperature above 25°C, which is high enough to decompose most of the initiator molecules to form free radicals. For another example, if a photoinitiator is used, the initiation conditions involve exposing the initiator to radiation of sufficiently low wavelength and sufficiently high intensity to decompose most of the initiator molecules to form free radicals. For another example, when the initiator is a redox initiator, the initiation conditions involve the presence of both an oxidant and a reductant in sufficiently high concentrations so that a significant number of free radicals are generated. Preferably, a thermal initiator is used. Preferably, the initiation conditions involve a temperature of 55°C or higher, more preferably 70°C or higher. That is, the suspension is preferably provided at a temperature below 40°C, and the initiator present does not generate a significant number of free radicals at the temperature. Then, preferably, step (b) involves raising the temperature to the initiation conditions.

[0099] After step (b), while polymerization is occurring, the extent of free radical polymerization in the vessel containing the suspension at any particular time can be characterized as follows.

[0100] Degree = 100*PM / TM

[0101] where PM is the mass of polymer formed by the free radical polymerization process, and TM is the total mass of monomer that has been added to the vessel up to that moment (including the initial monomer droplet and monomer added during the polymerization process).

[0102] Before the polymerization process begins, droplets are present in the suspension, and the droplets contain the vinyl monomer and the initiator. Preferably, the droplets are distributed throughout the aqueous medium. Preferably, the composition of the aqueous medium contains water in an amount of 90% by weight or more based on the weight of the aqueous medium; more preferably 95% by weight or more; more preferably 97% by weight or more. Compounds dissolved in water are considered to be part of the continuous liquid medium. Preferably, the volume average particle size of the droplets is 50 μm to 1,500 μm.

[0103] In the process of the present invention, once polymerization in the monomer droplets begins, the feed solution is added to the suspension. The action of adding the monomer to the suspension after polymerization begins is referred to herein as "gradual addition" or GA. The feed solution can be added at any rate. The rate at which the feed solution is added can be steady, or it can be faster at times than at other times. Addition of the feed solution can be accomplished in one continuous addition (which can be done quickly or slowly), or addition of the feed solution can be interrupted one or more times.

[0104] When the extent of reaction is at a point marked herein as "EXTSTART", the addition of feed solution is started. EXTSTART is between 0% and 50%, inclusive. Preferably, EXTSTART is 40% or less; more preferably 30% or less; more preferably 20% or less; more preferably 10% or less.

[0105] The extent of reaction "EXTSTOP" is the extent of reaction at which the last feed solution is added to the suspension. No more feed solution is added to the suspension after EXTSTOP. EXTSTOP is 5% to 100%. Preferably, EXTSTOP is 85% or less. Preferably, the amount

[0106] EXTDIFF = EXTSTOP - EXTSTART

[0107] 5% or more; more preferably 20% or more; more preferably 50% or more; more preferably 60% or more.

[0108] Preferably, the feed solution contains total vinyl monomers of all types in an amount of 75 wt % or more based on the weight of the feed solution; more preferably 85 wt % or more; more preferably 95 wt % or more; more preferably 99 wt % or more.

[0109] Preferably, the amount of the multifunctional monomer in the feed solution is 30% by weight or more based on the weight of the feed solution; preferably 40% by weight or more; more preferably 45% by weight or more; more preferably 50% by weight or more; more preferably 55% by weight or more; more preferably 60% by weight or more. When the multifunctional monomer is divinylbenzene (DVB), it is suitable to use industrial grade DVB, which is a mixture containing about 63% by weight of chemically pure DVB and about 37% by weight of ethylvinylbenzene (EVB) and other impurities totaling less than 1% by weight. When it is stated herein that a composition contains a certain amount of DVB, it is assumed that the composition contains EVB in addition to the specified amount of DVB, and the weight ratio of EVB:DVB is about 37:63. When such industrial grade DVB is used, the amount of industrial grade DVB in the feed solution is preferably 50% by weight or more based on the weight of the feed solution; more preferably 60% by weight or more; more preferably 70% by weight or more; more preferably 80% by weight or more; more preferably 90% by weight or more; more preferably 95% by weight or more.

[0110] Preferably, the feed solution either contains no initiator or contains an initiator in an amount of 100 ppm or less parts per million by weight; more preferably 10 ppm or less; more preferably 1 ppm or less.

[0111] Preferably, the feed solution either contains no water or contains water in an amount of 20 wt % or less based on the weight of the feed solution; more preferably 10 wt % or less; more preferably 3 wt % or less; more preferably 1 wt % or less; more preferably 0.3 wt % or less; more preferably 0.1 wt % or less.

[0112] Embodiments are also contemplated ("dispersion feed" embodiments) in which the feed solution is replaced by a feed composition that is a dispersion of monomer droplets in an aqueous medium. Such dispersions can be any type of dispersion, including, for example, suspensions, emulsions, microemulsions, or nanoemulsions. Such dispersions optionally contain one or more water-soluble polymers as described above, one or more surfactants, one or more dispersants, or mixtures thereof. In dispersion feed embodiments, emulsions are preferred. Among emulsions, preferred are emulsions containing one or more anionic surfactants.

[0113] In the dispersion feed embodiment, the total amount of monomers in the monomer composition is 5 wt % or more based on the weight of the feed composition; more preferably 10 wt % or more; more preferably 20 wt % or more; more preferably 40 wt % or more. In the dispersion feed embodiment, the total amount of monomers in the monomer composition is 60 wt % or less based on the weight of the feed composition; more preferably 55 wt % or less.

[0114] In the dispersion feed embodiment, it is useful to characterize the amount of the multifunctional vinyl monomer as a weight percent of the monomer content in the feed composition. In the dispersion embodiment, preferably, the amount of the multifunctional vinyl monomer is 50 wt % to 100 wt % based on the total weight of the monomers in the feed composition; more preferably 75 wt % to 100 wt %; more preferably 90 wt % to 100 wt %; more preferably 95 wt % to 100 wt %.

[0115] In the dispersion feed examples, suitable and preferred conditions for the feed during polymerization (degree of reaction, etc.) are the same as those described above.

[0116] The present invention also relates to a polymer bead assembly. The polymer bead assembly is preferably prepared by the method of the present invention. The polymer beads contain a polymer. The polymer beads are particles that are solid at 25°C and contain the polymer in an amount of 90% by weight or more based on the weight of the polymer particles; more preferably 95% by weight or more.

[0117] The polymer beads may be macroporous beads or gel beads. Gel beads are preferred.

[0118] Preferably, the volume average particle size of the polymer beads is 50 μm or more; more preferably 100 μm or more; more preferably 200 μm or more; more preferably 400 μm or more. Preferably, the volume average particle size of the polymer beads is 1,500 μm or less; more preferably 1,000 μm or less.

[0119] Preferred polymers in the polymer particles are polymers formed by free radical polymerization of the preferred vinyl monomers described above. Preferably, the polymer comprises polymerized units of styrenic monomers in an amount of 5 wt% or more based on the weight of the polymer; more preferably 25 wt% or more; more preferably 50 wt% or more; more preferably 75 wt% or more; more preferably 95 wt% or more. The types of monomers preferred as polymerized units of the polymer are the same as those preferably used in the polymerization process described above.

[0120] Preferred polymers have polymerized units of multifunctional vinyl monomers in an amount of 1 wt% or more based on the weight of the polymer; more preferably 1.5 wt% or more; more preferably 2 wt% or more. Preferred polymers have polymerized units of multifunctional vinyl monomers in an amount of 25 wt% or less based on the weight of the polymer; more preferably 20 wt% or less; more preferably 15 wt% or less; more preferably 11 wt% or less; more preferably 6 wt% or less.

[0121] Preferred polymers have polymerized units of monofunctional vinyl monomers in an amount of 99.7% by weight or less based on the weight of the polymer; more preferably 99.5% by weight or less; more preferably 99% by weight or less; more preferably 98.5% by weight or less. Preferred polymers have polymerized units of monofunctional vinyl monomers in an amount of 75% by weight or more based on the weight of the polymer; more preferably 80% by weight or more; more preferably 85% by weight or more; more preferably 90% by weight or more; more preferably 94% by weight or more.

[0122] The polymer in the polymer beads has a relatively uniform distribution of polymerized units of the multifunctional vinyl monomer. The uniformity of the distribution of polymerized units of the multifunctional vinyl monomer can be characterized as follows.

[0123] MVAV = average concentration of polymerized units of multifunctional vinyl monomers within a single bead (in moles / cubic micron)

[0124] T1000 = sequence of 1,000 linked polymerized monomer units

[0125] MVSEQ = for a specific T1000, the weight percent of polymerized units of multifunctional vinyl monomers based on the weight of T1000

[0126] MVRATIO=MVSEQ / MVAV

[0127] When T1000 is selected, any polymeric unit can be selected as the first unit of the sequence. Then, any polymeric unit that is covalently bound to the first polymeric unit can be selected as the second unit in the sequence. Likewise, each unit selected is covalently bound to the previous unit in the sequence. In a T1000 sequence, no polymeric unit can appear twice. When 1000 polymeric units have been selected, the T1000 sequence is complete. Another way to describe the process of selecting T1000 is to state that the first polymeric unit is picked up, and then a path is traced along the covalently bound polymeric units until the path is 1000 units long. The path is selected so that it does not cross itself. Each bead contains many T1000 sequences. The T1000 sequences are not physically changed or removed from the beads. The T1000 sequence is a tool to characterize the degree of uniformity of the polymer beads.

[0128] A bead is considered "homogeneous" if it has a relatively uniform distribution of polymerized units of a multifunctional vinyl monomer. That is, a bead is homogeneous if 90% or more, by sequence number, of all T1000 sequences in the bead have an MVRATIO of 1.5 or less. Preferred beads have a higher degree of homogeneity such that 90% or more, by sequence number, of all T1000 sequences in the bead have an MVRATIO of 1.25 or less.

[0129] In the bead collection of the present invention, most of the beads are uniform. That is, the amount of uniform beads is 90% by volume or more; more preferably 95% by volume or more; more preferably 99% by volume or more. More preferably, the amount of beads in which 90% or more of all T1000 sequences by sequence number have an MVRATIO of 1.25 or less is 90% by volume or more; more preferably 95% by volume or more; more preferably 99% by volume or more.

[0130] It is useful to consider the percentage of T1000 sequences by sequence number that have an MVRATIO of 0.5 or less. Preferably, 35% or less of the T1000 sequences by sequence number will have an MVRATIO of 0.5 or less. More preferably, 25% or less of the T1000 sequences by sequence number will have an MVRATIO of 0.5 or less.

[0131] The average sphericity of the polymer beads is preferably 0.8 or higher; more preferably 0.85 or higher; more preferably 0.9 or higher; more preferably 0.95 or higher.

[0132] A preferred use of the polymers produced in the free radical polymerization process of the present invention is in a conversion process for producing ion exchange resins. Ion exchange resins are classified into the following categories. Weak base anion exchange resins have primary, secondary or tertiary pendant amino groups. Strong base anion exchange resins have pendant quaternary amine groups. Weak acid cation exchange resins have pendant carboxylic acid groups. Strong acid cation exchange resins have pendant sulfonic acid groups. When any of these pendant functional groups have been attached to a polymer bead, the bead is referred to as a "functionalized resin."

[0133] Typically, when preparing weakly basic anion exchange resins from polymer beads (such as cross-linked polystyrene beads), the beads are advantageously halogenated, preferably halogenated, most preferably chloromethylated, and the ion-active exchange groups are subsequently attached to the halogenated copolymer. Typically, the halogenated reaction consists of the following steps: swelling the cross-linked addition copolymer with a halogenated agent (preferably bromomethyl methyl ether, chloromethyl methyl ether, or a mixture of formaldehyde and hydrochloric acid, most preferably chloromethyl methyl ether), and then reacting the copolymer and the halogenated agent in the presence of a Friedel-Crafts catalyst (such as zinc chloride, ferric chloride, or aluminum chloride). Typically, weakly basic anion exchange resins are prepared by reacting halogenated copolymers with ammonia, primary amines, or secondary amines. Typically, strongly basic anion exchange resins are prepared by reacting halogenated copolymers with tertiary amines.

[0134] Typically, when a strong acid cation exchange resin is prepared from polymer beads (such as cross-linked polystyrene beads), the beads are advantageously sulfonated. Typically, the beads are swollen using a suitable swelling agent, and the swollen beads are reacted with a sulfonating agent (such as sulfuric acid or chlorosulfonic acid or sulfur trioxide or a mixture thereof).

[0135] In addition to the polymer beads themselves, the collection of functionalized polymer beads normally also contains water. Normally, the process for preparing functionalized polymer beads involves contact between the functionalized polymer beads and water, and removing excess liquid water, but a large amount of water remains as part of the collection of functionalized polymer beads. It is expected that the water is adsorbed into the functionalized polymer beads. The amount of water is typically 30% to 90% by weight based on the weight of the collection of functionalized polymer beads.

[0136] It is contemplated that the polymer beads of the present invention may be used for a variety of purposes. The functionalized polymer beads will be used for many purposes where ion exchange resins are useful. For example, it is expected that the increased crush strength and osmotic stability of the functionalized polymer beads of the present invention will make these beads useful as water purification resins or catalysts in preferred uses. When the functionalized polymer beads of the present invention are used as catalysts, it is expected that the functionalized polymer beads of the present invention will increase the reaction rate of the catalyzed reaction. It is expected that the uniformity of the spatial distribution of polymerized units of multifunctional vinyl monomers in the functionalized polymer beads of the present invention will have the effect that more sites on the beads available for catalysis will also have an optimal concentration of polymerized units of multifunctional monomers to obtain an optimal reaction rate compared to previously known beads.

[0137] A preferred method of using the polymer beads of the present invention involves passing a liquid through a bed of polymer beads. That is, the collection of polymer beads is placed in a container that captures the polymer beads in place, the container having an inlet for the liquid to enter the container and having an outlet for the liquid to leave the container, the inlet allowing the liquid to flow through the container while in intimate contact with the polymer beads.

[0138] When the intended use is water purification, a functionalized resin is used to remove undesirable ions from water. The resin has a functional group (herein "functional group (iii)"). The resin is selected so that the functional group (iii) has a charge opposite to the charge on the undesirable ion. Prior to purification, the functional group (iii) is associated with a counter ion (herein referred to as "ion (iv)") that is not bound to the resin. The ion (iv) has the same charge as the undesirable ion. Preferably, the proportion of the functional group (iii) associated with the ion (iv) is 50 mol% or more; more preferably 75 mol% or more; more preferably 92 mol% or more.

[0139] In the "loading" step, the water to be purified is passed through the resin bed, and the undesirable ions in the water are loaded onto the functionalized polymer beads by associating with the functional group (iii) in exchange for ions (iv). Eventually, the resin is loaded at or near its capacity to retain the undesirable ions. Then, in order to remove the undesirable resin, the functionalized polymer beads are subjected to a "regeneration" step, in which a regeneration solution is passed through the resin bed. The regeneration solution contains dissolved ions, including ions (v) of the same type as ions (iv). The ions (v) replace the undesirable ions on the resin, and the undesirable ions are removed together with the regeneration solution.

[0140] Preferably, the cycle of loading and regeneration is repeated. That is, a new batch of water containing the same undesirable ions is passed through the resin bed to load the resin with the undesirable ions, and then the resin is regenerated as described above. Preferably, the loading and regeneration process is repeated 10 times or more; more preferably 20 times or more.

[0141] Repeated loading and regeneration cycles result in osmotic shock to the functionalized polymer beads, since the equilibrium water content (and therefore bead size) is a function of the specific counterion. Repeated cycling may cause some or all of the polymer beads to break. Preferably, the polymer beads of the present invention minimize such breakage.

[0142] The above discussion contemplates a single undesirable ion of a certain charge. If the water additionally contains a second undesirable ion of opposite charge to the first undesirable ion, it is contemplated that the water may be contacted with a second resin having functional groups of opposite charge to the functional groups on the first resin. The two resins may be used sequentially or may be mixed together.

[0143] For example, polymer beads functionalized with sulfonic acid groups are strong acid cation exchange resins ("SAC"). SAC can be used to remove unwanted sodium ions from water. Initially, the SAC can be in the hydrogen form. That is, more than half (by mole) of the sulfonate groups have a counter ion H + . An aqueous NaCl solution can then be passed through a bed of the SAC to exchange the hydrogen ions for sodium ions, so that the sodium ions remain on the SAC, placing the resin in the sodium form, in a process known as "loading" the resin. Eventually, the SAC reaches or approaches the limit of its ability to retain sodium ions. The SAC can then be regenerated, for example, by passing an aqueous solution of H2SO4 through the SAC bed to return the resin to the hydrogen form. Such cycles of loading followed by regeneration place the resin beads under osmotic pressure because the sodium form and the hydrogen form have different equilibrium water contents, and the osmotic shock of repeated cycles tends to rupture some of the beads.

[0144] For another example, the polymer beads functionalized with quaternary ammonium groups are strong base anion exchange resins ("SBA"). SBA can be used to remove unwanted chloride ions from water. Initially, the SBA can be in the hydroxide form. That is, more than half (by mole) of the quaternary ammonium groups have a counterion OH - . An aqueous NaCl solution can then be passed through the bed of the SBA to exchange the hydroxide ions for chloride ions so that the chloride ions are retained on the SBA in a process known as "loading" the resin. Eventually, the SBA reaches or approaches the limit of its ability to retain chloride ions. The SBA can then be regenerated, for example, by passing an aqueous NaOH solution through the SBA bed to return the resin to the hydroxide form. This cycle of loading followed by regeneration places the resin beads under osmotic pressure because the chloride form and the hydroxide form have different equilibrium water contents, and the osmotic shock of repeated cycles tends to rupture some of the beads.

[0145] Similar loading and regeneration processes can be performed by these or other resins to remove these or other ions. Weak acid cation exchange resins or strong acid cation exchange resins can be used to remove monovalent or multivalent cations. Weakly basic anion exchange resins or strong basic cation exchange resins can be used to remove undesirable monovalent and / or multivalent anions. Any of these processes involving loading and regeneration cycles creates osmotic stress on the resin beads.

[0146] When the intended use is water purification, the crush resistance and osmotic shock resistance make the resin of the present invention advantageous. Because the beads have a less tendency to break, a given bead assembly will have a longer service life before the beads need to be replaced. Moreover, when the beads break, the fragments fill the interstitial spaces between the beads, which hinders the flow of water through the bead bed, resulting in an increased pressure drop from the inlet to the outlet of the bed in the water. In addition, the broken beads can also cause channeling, which reduces the amount of water that the bead bed can handle, thus making it necessary to regenerate the beads more frequently, which in turn increases the cost of chemicals and increases the osmotic stress on the beads.

[0147] When the intended use of the resin is as a catalyst, the functionalized collection of polymer beads (referred to herein as a "resin") is employed by contacting the resin with one or more reactants and allowing a chemical reaction involving the one or more reactants to occur to produce one or more products. In a preferred catalyst embodiment, the collection of polymer beads is functionalized with sulfonic acid groups to produce a SAC. When used as a catalyst, the SAC is referred to as an "acid catalyst."

[0148] Resins intended for use as catalysts may be characterized by their moisture holding capacity (MHC). The MHC is the amount of water present in the polymer bead assembly when the bulk of the liquid water has been separated from the beads and the beads have been allowed to equilibrate with air having a relative humidity of 100%. Preferably, the MHC of the resin intended for use as a catalyst is 90 wt% or less based on the total weight of the resin bead assembly including the beads and water; more preferably 80 wt% or less. Preferably, the amount of water present in the resin prior to contact with acetone and phenol is 50 wt% or more based on the weight of the resin; more preferably 60 wt% or more.

[0149] The preferred reactants are acetone and phenol, which react to produce 2,2-bis(4-hydroxyphenyl)propane (also known as bisphenol A). It is expected that two moles of phenol react with one mole of acetone to produce one mole of bisphenol A and one mole of water. In the formation of bisphenol A, the preferred resin catalyst is a SAC resin. The resin may or may not react with an accelerator prior to contact with acetone and phenol. In a preferred embodiment, the resin is reacted with an accelerator prior to contact with acetone and phenol. The preferred accelerator has both an amine group and a thiol group. Preferably, the amine group on the accelerator is linked to a sulfonic acid group on the resin. Preferably, the molar percentage of sulfonic acid groups linked to the amine group of the accelerator is 5% to 50%. Preferably, water is removed from the collection of resin beads prior to contact with acetone and phenol, for example by rinsing with phenol. Preferably, the water content in the collection of polymer beads is 2% by weight or less based on the collection of polymer beads immediately prior to contact with acetone and phenol; more preferably 1% by weight or less.

[0150] Preferably, the resin is at a temperature of 55°C or higher; more preferably 60°C or higher when the resin is contacted with phenol and acetone.

[0151] Resistance to crushing is also an advantage when the intended use is catalysis.The lifetime of the resins of the invention will be higher and the reduced level of fine particles will allow the reactants to pass through the resin bed at a lower pressure drop.

[0152] The following are examples of the present invention.

[0153] The following terms, abbreviations and materials are used:

[0154] Jetted = monomer droplets are introduced into an aqueous medium using the spraying procedure described in US 4,444960 and US 4,623,706

[0155] tBC = 4-tert-butylcatechol; some tBC is present in the grade of DVB used.

[0156] DVB = divinylbenzene, produced and supplied by The Dow Chemical Company. The grade of DVB used was a mixture containing 63 wt% pure divinylbenzene and about 37 wt% ethylvinylbenzene. The percentages of DVB listed below refer to the amount of pure DVB. When DVB was present, it was assumed that EVB was also present in a weight ratio of EVB:DVB of about 37:63. DVB contained about 1000 ppm by weight of tBC.

[0157] tBC-free DVB = DVB without tBC. To prepare tBC-free DVB, tBC was stripped from the indicated DVB fractions through a series of 4% NaOH batch washes.

[0158] CMMC = carboxymethyl methylcellulose, manufactured and supplied by The Dow Chemical Company.

[0159] PVOH=SELVOL TM 523 Polyvinyl alcohol, from Sekisui Specialty Chemicals

[0160] HEMC=WALOCEL TM MKX 15000PF 01 Hydroxyethylcellulose from The Dow Chemical Company

[0161] SBA = Strong Base Anion Exchange Resin; Styrene / DVB copolymer functionalized with quaternary ammonium groups

[0162] SAC = Strong Acid Cation Exchange Resin; Styrene / DVB copolymer functionalized with sulfonic acid groups

[0163] Tris = tris(hydroxymethyl)aminomethane, 100% solid, supplied by Fisher Scientific, used as a 20% by weight aqueous solution

[0164] PADMAC = 20 wt% aqueous solution of poly(diallyldimethylammonium chloride), also known as poly(DADMAC).

[0165] Gelatin = Animal-based gelatin, isoelectric point is about 8.5

[0166] VPBA = 4-vinylphenylboronic acid

[0167] BPO = benzoyl peroxide, purity 75% by weight

[0168] DI water = deionized water

[0169] Dichromate: = sodium dichromate dihydrate solution, concentration = 70 wt% dihydrate in water

[0170] GA = Gradual Addition

[0171] Ambient temperature = about 23°C

[0172] Eight suspension polymerization protocols were used, labeled A, B, D, E, F, G, and H. The protocols are distinguished by the following protocols. After the copolymer beads were formed, they were functionalized using the method listed in the last column. The details of the functionalization method are shown in the table below.

[0173]

[0174] 1. Water-soluble polymers in aqueous media

[0175] 2. Inhibitors in aqueous media

[0176] 3. Droplet formation by spraying or by agitation

[0177] 4. Total weight percent of DVB in the entire process, as a percentage of total monomer weight.

[0178] In preparing the droplet mixture or aqueous medium described below, some portions of the mixture are sometimes heated to above 25° C. to achieve good mixing. However, when the droplets are formed and suspended in the aqueous medium, all ingredients are at ambient temperature.

[0179] When the copolymer is converted to a SAC resin, the polymer beads containing the copolymer are sulfonated by a standard sulfonation method using sulfuric acid to achieve a degree of substitution such that at least 95 mol % of the aromatic rings on the polymerized units of the monofunctional vinyl monomer have sulfonate groups, based on the total polymerized units of the monofunctional vinyl monomer.

[0180] The crush strength is measured as follows. The functionalized polymer beads are exposed to air at 100% humidity and 50°C for 4 days. The beads are then covered with deionized water and stored at room temperature (about 23°C) for one hour or more. A single bead is placed on one plate of a compression tester at room temperature and the bead is covered with a drop of water. The plates are brought together at 6.0 mm / min until the particle breaks and the peak force is recorded. The procedure is repeated for at least 30 beads and the average peak force is reported as the "crush strength". The test apparatus is a TCD 200 Chatillon with a medium to low speed motor (2.5 to 63.5 mm / min). TM Force Tester. The dynamometer is model DFGS10. The crushing strength is reported in grams of force per bead (g / bd).

[0181] The osmotic stability (OS) is measured as follows. The functionalized polymer beads are conditioned by contact with an aqueous NaCl solution at ambient temperature (about 23°C). The NaCl solution is decanted and the wet resin is passed through a mesh screen to produce a resin sample with a diameter of 500 μm to 710 μm. The resin is then placed in a vertical straight-walled glass column. A single cycle is as follows: the fluid is drained from the column by gravity; the resin in the column is contacted with solution #1; the column is backwashed with water; the fluid is drained from the column by gravity; the resin in the column is contacted with solution #2; the fluid is drained from the column and the column is backwashed with water. The test is repeated for 50 cycles. Solution #1 is an aqueous H2SO4 solution. Solution #2 is an aqueous NaOH solution. The cycles of exposure to different solutions cause some particles to break. After the exposure cycles, the beads are placed on a screen that allows objects with a diameter of less than 500 μm to pass through. The material retained on the screen is considered to be a complete bead, and the material passing through the screen is considered to be fragments of broken beads. The osmotic stability is

[0182] OS(%)=100XW 碎片 / (W 完整 +W 碎片 )

[0183] Where W 碎片 = weight of the fragment, and W 完整 = weight of intact beads. Lower OS values ​​are more desirable.

[0184] The storage stability of the functionalized resin samples was tested as follows. The resin was separated from the bulk water and allowed to equilibrate with air at ambient temperature and 100% relative humidity. The resin was then placed in a closed vial and stored at ambient temperature for 30 days. The resin was then thoroughly mixed with DI water at a weight ratio of 3 parts water to 1 part resin. The water was removed by filtration and the water was tested for conductivity and absorbance at a wavelength of 350 nm using standard instrumentation.

[0185] In all cases except G, the weight ratio of the droplet components to the aqueous phase components was 0.61:1. In case G, the weight ratio of the droplet components to the aqueous phase components was 1:1. When DVB was added gradually during polymerization, it was added continuously within the range of degrees shown in the table of Example R1 below. The DVB addition was continuous, but the rate during the addition process was varied.

[0186] The composition of the starting droplets in the following examples (immediately before initiation of polymerization) is as follows. Amounts are weight % based on the weight of the monomer droplets. (All samples with the same prefix use the same aqueous medium composition. For example, Examples A-2a(1), A-2A(2), and A-2b all use the same aqueous medium composition, labeled "A-2"). The total weight of each monomer droplet composition is 100%. Samples with the suffix "Comp" are used in the comparative method. BPO is present in all starting droplets as an initiator.

[0187]

[0188]

[0189] The composition of the aqueous medium in the following examples is as follows. The amounts are in weight percent based on the weight of the aqueous medium. In all cases, the aqueous phase concentration of the stabilizer is such that the number percentage of beads having a sphericity of 0.8 or greater is at least 99% based on the total number of beads. In all cases, the aqueous or monomer phase concentration of the stabilizer is such that the number percentage of beads having a sphericity of 0.8 or greater is at least 99% based on the total number of beads. In all cases, the aqueous phase concentration of the latex inhibitor is such that the weight percentage of the emulsion polymer at the end of the reaction is less than 0.5% based on the total weight of the polymer beads.

[0190] The harmonic mean diameter of the final polymer beads formed by spraying was 430-470 microns. For droplets formed by agitation, the harmonic mean diameter of the final polymer beads was 490-650 microns.

[0191]

[0192]

[0193]

[0194] Comparative Example A1-Comp using Scheme A (no monomer addition after polymerization initiation).

[0195] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in a degree of conversion of 80%-85% in 330-390 minutes. Once the conversion to polymer was in the range of 80%-85%, the pH was adjusted by adding Tris to the reactor - so that the final pH was in the range of 8-9. The reaction system was heated to 97°C. After 1 hour at 97°C, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature. Two identical polymerizations were performed.

[0196] Examples A-2a and A-2b of Scheme A were also used.

[0197] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in a conversion of 80% to 85% in 390 to 550 minutes. Once the reaction temperature was reached, DVB was fed to the reactor within the range shown in the table of Example R1 below, where the feed rate of DVB was varied over time. Two repeated polymerizations of A-2a were performed, labeled A-2a(1) and A-2a(2).

[0198] Once the conversion to polymer was in the range of 60%-75%, Tris was added to the reactor so that the final pH was in the range of 8-9. The reaction system was heated to 97°C within 60 minutes of the Tris addition. After 1 hour, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature.

[0199] Example A-2c of Scheme A was also used.

[0200] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in a conversion of 80% to 85% in 390 to 550 minutes. Once the reaction temperature was reached, DVB was fed to the reactor to the extent shown in the table of Example R1 below, wherein the feed rate of DVB was varied over time.

[0201] Once the conversion to polymer was in the range of 60%-75%, Tris was added to the reactor so that the final pH was in the range of 8-9. The reaction system was heated to 97°C within 60 minutes of the Tris addition. After 1 hour, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature.

[0202] Comparative Example B1-Comp using Scheme B (no monomer addition after polymerization initiation).

[0203] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in 80%-85% conversion in 480-560 minutes. Once the reaction temperature was reached, a feed of 0.1% tBC in water was started to the reactor. The tBC feed rate was varied over time to simulate the tBC feed that normally accompanies the DVB feed.

[0204] tBC was gradually added from the range of 0% to 57%. Before initiation of polymerization, the tBC concentration in the monomer droplets was 0.0055 wt%. At the end of the tBC feed, the tBC concentration in the monomer droplets (partially or completely converted to polymer) was 0.0101 wt%.

[0205] Once the conversion to polymer was in the range of 80%-85%, the pH was adjusted by adding Tris to the reactor so that the final pH was in the range of 8-9. The reaction system was heated to 97°C. After 1 hour, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature.

[0206] Examples B-2a, B-2b, B-2c, B-2d, B-2e and B-2f of Scheme B were also used.

[0207] Duplicate samples of B-2b were prepared and labeled B-2b(1) and B-2b(2).

[0208] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in a conversion of 80% to 85% in 420 to 600 minutes. Once the reaction temperature was reached, DVB was fed to the reactor within the range shown in the table of Example R1 below, wherein the feed rate of DVB was varied over time.

[0209] Once the conversion to polymer was in the range of 60%-85%, Tris was added to the reactor so that the final pH was in the range of 8-9. The reaction system was heated to 97°C within 60 minutes of the Tris addition. After 1 hour, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature.

[0210] Comparative Example C1-Comp using Scheme C (no monomer addition after polymerization initiation).

[0211] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in 80%-85% conversion in 330-390 minutes. Once the reaction temperature was reached, Tris was added to the reactor so that the final aqueous pH was in the range of 8-9. Once the conversion was in the range of 80%-85%, the system was heated to 97°C. After 1 hour at 97°C, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature.

[0212] Example C-2 using Scheme C

[0213] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in a conversion of 80% to 85% in 420 to 600 minutes. Once the reaction temperature was reached, DVB was fed to the reactor within the range shown in the table of Example R1 below, wherein the feed rate of DVB was varied over time.

[0214] Once the conversion was in the range of 60%-85%, Tris was added to the reactor so that the final pH was in the range of 8-9. The reaction system was heated to 97°C within 60 minutes of the Tris addition. After 1 hour, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature.

[0215] Comparative Example D1-Comp using Scheme D (no monomer added after polymerization initiation).

[0216] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in a conversion of 80%-85% in 420-600 minutes. Once the conversion to polymer was in the range of 80%-85%, the pH was adjusted by adding Tris to the reactor - so that the final pH was in the range of 8-9. The reaction system was heated to 97°C. After 1 hour, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature. Two identical polymerizations were performed.

[0217] Example D-2a of Scheme D was used.

[0218] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in a conversion of 80% to 85% in 390 to 550 minutes. Once the reaction temperature was reached, DVB was fed to the reactor within the range shown in the table of Example R1 below, wherein the feed rate of DVB was varied over time. Two repeated polymerizations were performed, labeled D-2a(1) and D-2a(2).

[0219] Once the conversion to polymer was in the range of 20%-30%, Tris buffer was added to the reactor so that the final pH was in the range of 8-9. When the conversion reached 80%-85%, additional Tris buffer was added so that the final pH was in the range of 8-9. The reaction system was then heated to 97°C within 60 minutes of the addition of Tris. After 1 hour, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature.

[0220] Example D-2b using protocol D. The same protocol as in D-2a was used except that DVB was added gradually over the range of extents shown in the table of Example R1 below. Two repeated polymerizations were performed, labeled D-2b(1) and D-2b(2).

[0221] Comparative Example E-1 Comp using Scheme E (no monomer was added after the polymerization was initiated).

[0222] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in a conversion of 80%-85% within 210-270 minutes. Once the conversion to polymer was in the range of 80%-85%, the reaction system was heated to 92°C. After 1 hour, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature.

[0223] Example E-2 of Scheme E was used.

[0224] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in a conversion of 80% to 85% in 300 to 360 minutes. Once the reaction temperature was reached, DVB was fed to the reactor within the range shown in the table of Example R1 below, wherein the feed rate of DVB was varied over time.

[0225] Once the conversion to polymer was in the range of 80%-85%, the reaction system was heated to 92° C. After 1 hour, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature.

[0226] Comparative Example F1-Comp using Scheme F (no monomer added after polymerization initiation).

[0227] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in a conversion of 80%-85% in 300-360 minutes. Once the conversion to polymer was in the range of 80%-85%, the pH was adjusted by adding Tris to the reactor - so that the final pH was in the range of 8-9. The reaction system was heated to 97°C. After 1 hour, the system was cooled to ambient temperature, and the beads were dehydrated, washed with water, and dried at ambient temperature.

[0228] Example F-2 using Scheme F.

[0229] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in a conversion of 80% to 85% in 330 to 390 minutes. Once the reaction temperature was reached, DVB without tBC was fed to the reactor within the range shown in the table of Example R1 below, where the feed rate of DVB was varied over time.

[0230] Once the conversion to polymer was in the range of 80%-85%, Tris was added to the reactor so that the final pH was in the range of 8-9. The reaction system was heated to 97°C within 60 minutes of the Tris addition. After 1 hour, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature.

[0231] Comparative Example G1-Comp using Scheme G (no monomer added after polymerization initiation).

[0232] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in a conversion of 80%-85% within 300-360 minutes. Once the conversion of the polymer was in the range of 80%-85%, the reaction system was heated to 90°C. After 3 hours, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature.

[0233] Example G-2 using Scheme G

[0234] The reaction mixture was subjected to aqueous suspension polymerization as follows. The combination of reaction temperature and BPO concentration was selected to result in a conversion of 80% to 85% in 420 to 600 minutes. Once the reaction temperature was reached, DVB was fed to the reactor within the range shown in the table of Example R1 below, wherein the feed rate of DVB was varied over time.

[0235] Once the polymer conversion was in the range of 80%-85%, the reaction system was heated to 90° C. After 3 hours, the system was cooled to ambient temperature and the beads were dehydrated, washed with water, and dried at ambient temperature.

[0236] Example R1: Results of testing the physical stability of SAC resin.

[0237] The copolymers prepared using the above protocol were converted to SAC resins and tested as described above. The results are as follows. Where duplicate samples were tested, the average results are shown.

[0238] Process = refers to whether the polymerization process has a gradual addition (GA) step of the present invention.

[0239] Initial DVB = amount of DVB in the monomer droplet before initiation of polymerization (by weight, based on the weight of the monomer droplet)

[0240] Final DVB = the number of polymerized units of DVB in the final polymer, by weight, based on the total weight of all monomers used throughout the process (including the initial droplets and the DVB fed during the polymerization)

[0241] EXTSTART = reaction extent at the start of DVB feed

[0242] EXTSTOP = Extent of reaction at the end of DVB feed

[0243] DIAM = harmonic mean diameter of polymer beads

[0244]

[0245]

[0246] Example R2: Test results of Scheme E samples.

[0247] A strongly base anion (SBA) exchange resin is prepared from the copolymer of Scheme E by standard methods of chloromethylation using chloromethyl ether followed by amination using trimethylamine such that at least 95 mole percent of the aromatic rings on the polymerized units of the monofunctional vinyl monomer have attached amine-containing groups, based on the total polymerized units of the monofunctional vinyl monomer.

[0248] SBA resin was tested as in Example AR. The results are as follows:

[0249]

[0250] Example R3: Catalytic Results

[0251] Various functionalized resin samples were tested for their activity in catalyzing the reaction between phenol and acetone to produce bisphenol A (BPA). Catalytic activity is characterized by the time to reach 60% conversion ("T60%"). Shorter times reflect higher levels of catalytic activity.

[0252] The catalytic reaction was carried out as follows: The resin was rinsed with phenol to remove moisture from the beads. Phenol was added to a glass reactor and heated at 50°C to melt the phenol. Dry resin loaded with a promoter was added to the reactor and allowed to swell in the phenol. The reactor temperature was adjusted to a temperature between 45°C and 80°C. Acetone was added to the reactor. At multiple time intervals, a small amount of liquid sample in the reactor was removed by pipette, placed in a vial, and mixed with an excess of N-methyl-N-(trimethylsilyl)trifluoroacetamide. The vial was stored at 60°C for 30 minutes, then cooled to ambient temperature and then tested for BPA content by gas chromatography.

[0253] The catalytic results are as follows: All samples shown have a total amount of DVB polymerized units of 4.65%.

[0254] Examples A-2a A-2b A-2c C-1Comp T60%(min) 52 52 47 71

[0255] Samples A-2a, A-2b and A-2c prepared using gradual addition according to the present invention had much shorter times to 60% conversion than the comparative sample.

[0256] Example R4: Results of 30-day storage at ambient temperature

[0257] The storage results are as follows:

[0258] Examples: A-1Comp A-2a A-2b C-1Comp C-2 Conductivity(μS) 169 127 160 189 126 Absorbance 0.225 0.165 0.171 0.235 0.137

[0259] Each example resin exhibits lower conductivity and absorbance than its corresponding comparative example. That is, samples A-2a and A-2b exhibit lower conductivity and absorbance than comparative A-1Comp. Similarly, sample C-2 has lower conductivity and absorbance than comparative C-1Comp. This result indicates that the example resins have greater stability during storage.

Claims

1. A collection of polymer beads, wherein the beads comprise (i) 75 to 99 wt. % of polymerized units of monofunctional vinyl monomers, based on the weight of the beads, and (ii) from 1 to 25 wt. % of polymerized units of a polyfunctional vinyl monomer, based on the weight of the beads, in, In each bead, the average molar concentration of polymerized units of the multifunctional vinyl monomer per cubic micrometer is MVAV; where, within each bead, T1000 is a sequence of 1,000 uniquely linked polymerized monomer units; wherein, within each T1000, MVSEQ is the weight percent of polymerized units of multifunctional vinyl monomers, based on the weight of T1000; Where MVRATIO = MVSEQ / MVAV; and wherein 90% by volume or more of said beads are homogeneous beads, wherein homogeneous beads are beads wherein 90% or more of all T1000 sequences have an MVRATIO of 1.5 or less, The aggregate of polymer beads is obtained by a method comprising the following steps: (a) providing an aqueous suspension of monomer droplets comprising an initiator, a monofunctional vinyl monomer, and a polyfunctional vinyl monomer; (b) initiating polymerization of the monomers in the monomer droplets; (c) adding a monomer feed solution to the suspension while polymerization of the monomer in the monomer droplets is occurring, wherein the addition is started when the degree of polymerization of the monomer in the monomer droplets (EXTSTART) is 0%, wherein the adding is terminated when the degree of polymerization of the monomer in the monomer droplets (EXTSTOP) is 5% to 24% after EXTSTART; wherein the feed solution comprises the monomer in an amount of 90 wt % to 100 wt % based on the weight of the feed solution; wherein the feed solution comprises a multifunctional vinyl monomer in an amount of 50 wt % to 100 wt % based on the weight of the feed solution, wherein before initiating polymerization, the amount of the multifunctional vinyl monomer in the droplet as a weight percentage of the total monomers MFMPRIROR is 0.1% or more and 10% or less, Where MFMRATIO = 100 * MFMPRIOR / MFMTOTAL Where MFMTOTAL is the total weight percent of multifunctional monomers used in the entire polymerization process, including multifunctional monomers present before initiation and multifunctional monomers added after initiation, Wherein MFMRATIO is 10% or more and 80% or less.

2. The aggregate of polymer beads according to claim 1, wherein In 90% by volume or more of the beads, 90% or more of all T1000 sequences had an MVRATIO of 1.25 or less.

3. The aggregate of polymer beads according to claim 1, wherein The monofunctional monomer includes styrene.

4. The aggregate of polymer beads according to claim 1, wherein The multifunctional monomer includes divinylbenzene.

5. The aggregate of polymer beads according to claim 1, wherein 35% or less of the T1000 sequences had an MVRATIO of 0.5 or less.

6. The aggregate of polymer beads according to claim 1, wherein The polymer beads have an average particle diameter of 50 μm or more.

7. The aggregate of polymer beads according to claim 1, wherein The polymer beads have an average particle diameter of 100 μm or more.

8. The aggregate of polymer beads according to claim 1, wherein The polymer beads have an average particle diameter of 200 μm or more.

9. The aggregate of polymer beads according to claim 1, wherein The polymer beads have an average particle diameter of 400 μm or more.

10. The aggregate of polymer beads according to claim 1, wherein The polymer beads have an average particle size ranging from 50 μm to 1,500 μm.

11. The aggregate of polymer beads according to claim 1, wherein The polymer beads have an average particle size ranging from 400 μm to 1,000 μm.

12. The aggregate of polymer beads according to claim 1, wherein The polymer beads are gel beads.

13. The aggregate of polymer beads according to claim 1, wherein The collection of polymer beads comprises from 80% to 99% by weight, based on the weight of the beads, of polymerized units of a monofunctional vinyl monomer.

14. The aggregate of polymer beads according to claim 1, wherein The collection of polymer beads comprises from 85% to 99% by weight, based on the weight of the beads, of polymerized units of a monofunctional vinyl monomer.

15. The aggregate of polymer beads according to claim 1, wherein The collection of polymer beads comprises from 90% to 99% by weight, based on the weight of the beads, of polymerized units of a monofunctional vinyl monomer.

16. The aggregate of polymer beads according to claim 1, wherein The collection of polymer beads comprises from 94% to 99% by weight, based on the weight of the beads, of polymerized units of a monofunctional vinyl monomer.

17. The aggregate of polymer beads according to claim 1, wherein: The aggregate of polymer beads comprises from 1 wt% to 15 wt% of polymerized units of a multifunctional vinyl monomer, based on the weight of the beads.

18. The aggregate of polymer beads according to claim 1, wherein The aggregate of polymer beads comprises from 1 wt% to 11 wt% of polymerized units of a multifunctional vinyl monomer, based on the weight of the beads.

19. The aggregate of polymer beads according to claim 1, wherein: The aggregate of polymer beads comprises from 1 wt% to 6 wt% of polymerized units of a multifunctional vinyl monomer, based on the weight of the beads.

Citation Information

Patent Citations

  • Production of copolymers

    US3792029A

  • Polymer blends with improved hydrolytic stability

    US4444960A

  • Process for preparing uniformly sized polymer particles by suspension polymerization of vibratorily excited monomers in a gaseous or liquid stream

    US4623706A

  • Preparation method of 10-micron to 100-micron chloromethylated crosslinked polystyrene microspheres

    CN102875719A

  • Green preparation method of cation exchange resin

    CN106632804A